Assessing the Influence of Safety Culture to Employee Safety Performance Mediated by Safety Communication in Coal-Fired Power Plant - Bambang Jiwantoro (Green Publisher Indonesia, 2024)
This study analyzes the effect of safety culture on employee safety performance at a Coal Fired Power Plant (CFPP) in Java, as well as the mediating role of safety communication and moderating role of service years. This study aims to investigate the direct and indirect effects between the variables of safety culture, safety communication and employee safety performance. In addition, the study also explored the moderating role of service year in the relationship between safety culture and employee safety performance. Data was obtained from distributing questionnaires to CFPP employees using a stratified sampling method. SmartPLS SEM. The findings reveal that safety culture does not have a significant direct effect on employee safety performance. However, safety communication significantly mediates the relations between safety culture and employee safety performance. The service year does not moderate the relationship between safety culture and employee safety performance This indicates that other factors such as continuous training, reward system, and work environment may be more influential in this context.